Identitas nasional dalam era globalisasi: tantangan dan strategi penguatan di indonesia - Khutmala, Rohadatul Firda (Maliki Interdisciplinary Journal, 2026)
National identity is a distinctive characteristic that distinguishes a nation from others, both in terms of culture, values, and ideology. In the Indonesian context, national identity is rooted in diversity united in the spirit of Bhinneka Tunggal Ika (Unity in Diversity). However, the development of globalization has had a significant impact on the existence of national identity, especially among the younger generation. This study aims to analyze the concept of national identity, its forming factors, as well as the challenges and strategies for strengthening it in the era of globalization. The method used is a literature study by reviewing various scientific sources from the UIN Maulana Malik Ibrahim Malang repository and other related supporting scientific sources. The results of the study indicate that Indonesia’s national identity needs to be strengthened through character education, cultural preservation, and the wise use of technology.